2021
DOI: 10.3389/fendo.2021.664766
|View full text |Cite
|
Sign up to set email alerts
|

Collagen I Induces Preeclampsia-Like Symptoms by Suppressing Proliferation and Invasion of Trophoblasts

Abstract: Preeclampsia is a common obstetric disorder affecting 2-8% of pregnancy worldwide. Fibrosis is an important histological change occurring in preeclamptic placenta, and might depend on the excess deposition of collagen I. However, the role of fibrotic placenta and collagen I in the pathogenesis of preeclampsia remains unclear. Therefore, we analyzed the collagen deposition and the expression of Collagen I in human placenta by Masson staining, Sirius red staining and western blotting. Further, the role of collag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Thus, morphological alterations have been reported in both the placenta and kidney under preeclamptic conditions [ 36 , 37 ], and histopathological examination of the kidney has been suggested as a predictive tool for prognostic purposes [ 38 ]. Collagen deposition in the placenta has been found in the reduced uteroplacental perfusion pressure (RUPP) preeclampsia animal model [ 39 ], and excess collagen deposition originated preeclampsia-like features in pregnant mice [ 40 ]. Interestingly, serum from PE patients has been shown to contain vasoactive substances that induce deposition of extracellular matrix components including collagen [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, morphological alterations have been reported in both the placenta and kidney under preeclamptic conditions [ 36 , 37 ], and histopathological examination of the kidney has been suggested as a predictive tool for prognostic purposes [ 38 ]. Collagen deposition in the placenta has been found in the reduced uteroplacental perfusion pressure (RUPP) preeclampsia animal model [ 39 ], and excess collagen deposition originated preeclampsia-like features in pregnant mice [ 40 ]. Interestingly, serum from PE patients has been shown to contain vasoactive substances that induce deposition of extracellular matrix components including collagen [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, impaired trophoblast proliferation and migration can lead to improper remodeling of maternal spiral arteries, which is one of the main factors contributing to preeclampsia. It is noteworthy that an excess of collagen I led to preeclampsia-like features in pregnant mice since it suppresses trophoblast proliferation and invasion through inhibition of ERK phosphorylation and the WNT/β-catenin signaling pathway [ 43 ]. These authors also reported an increase in the collagen I deposition as well as a higher gene and protein expression of collagen in the preeclamptic placenta [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that an excess of collagen I led to preeclampsia-like features in pregnant mice since it suppresses trophoblast proliferation and invasion through inhibition of ERK phosphorylation and the WNT/β-catenin signaling pathway [ 43 ]. These authors also reported an increase in the collagen I deposition as well as a higher gene and protein expression of collagen in the preeclamptic placenta [ 43 ]. Collagen deposition has also been evaluated in first-term villi and full-term placentas, and the results obtained by Masson’s trichrome staining and western blot also showed higher levels of collagen in preeclampsia patients [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The development of placental fibrosis in preeclampsia is a well-studied process [ 24 , 25 ]. Collagen-I deposition is increased in fibrosis leading to preeclampsia [ 26 ]. Collagen-I expression was increased in our late-onset preeclampsia samples compared to our healthy placental samples suggesting an increase in fibrosis.…”
Section: Discussionmentioning
confidence: 99%